Under Prescription of Epinephrine to Medicaid Patients in the Pediatric Emergency Department. (June 2019) - Owusu-Ansah, Sylvia; Badaki, Oluwakemi; Perin, Jamie; Stevens, Martha; Anders, Jennifer; Wood, Robert
Objective . To describe pediatric Medicaid patients with pediatric emergency department (PED) visits for anaphylaxis who received epinephrine auto-injector (EAI) prescriptions in the ED versus those who did not; and to compare patients who filled their prescriptions versus those who did not. Methods . We conducted a cross-sectional study of Medicaid patients aged 0 to 21 years presenting to 2 PEDs, with symptoms meeting the National Institute of Allergy and Infectious Diseases criteria for anaphylaxis, between July 2012 and July 2014. Results. We identified 86 patients across the 2 hospitals with a confirmed diagnosis of anaphylaxis in the PED. Of these, 55 (64%, 95% confidence interval [CI] = 53% to 74%) received a prescription for an EAI during their ED visit. Forty-two (68%; 95% CI = 56% to 80%) received a prescription for EAI in Hospital 1 versus 13 (54%; 95% CI = 33% to 74%) in Hospital 2. Medicaid prescription fill rates were available for Hospital 1. Of the 42 who received an EAI prescription, 36 (86%; 95% CI = 75% to 96%) filled these prescriptions with Medicaid. Of the 20 (32%) out of 62 patients with anaphylaxis who did not receive prescriptions for an EAI, only 5 had previously filled prescriptions for epinephrine. Conclusion . Previous Medicaid patient prescription adherence data suggested that these patients would have a low EAI prescription fill rate. We found Medicaid patients who received prescriptions for an EAI after the ED visit for anaphylaxis filled them; however, a considerable proportion of anaphylaxis visits had no EAI prescription provided at discharge.